2018
DOI: 10.1186/s12885-018-4370-1
|View full text |Cite
|
Sign up to set email alerts
|

microRNA-451a regulates colorectal cancer proliferation in response to radiation

Abstract: BackgroundColorectal cancer (CRC) is a leading cause of cancer-related death. The biologic response of CRC to standard of care adjuvant therapies such as chemotherapy and radiation are poorly understood. MicroRNAs (miRs) have been shown to affect CRC progression and metastasis. Therefore, we hypothesized that specific miRs modulate CRC response to chemoradiation.MethodsIn this study, we used miR expression profiling and discovered a set of microRNAs upregulated rapidly in response to either a single 2 Gy dose … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 34 publications
1
34
0
Order By: Relevance
“…However, overexpression of miR‐21 can promote the radiation resistance of NSCLC cells . In colorectal cancer cells, miR‐451a can regulate the cell proliferation in response to radiation . It has been reported that miR‐124 can enhance the radiation‐induced apoptosis of NSCLC cells via inhibition of STAT3 .…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…However, overexpression of miR‐21 can promote the radiation resistance of NSCLC cells . In colorectal cancer cells, miR‐451a can regulate the cell proliferation in response to radiation . It has been reported that miR‐124 can enhance the radiation‐induced apoptosis of NSCLC cells via inhibition of STAT3 .…”
Section: Introductionsupporting
confidence: 65%
“…It has been reported that radiation greater than 5 Gy can significantly inhibit the proliferation of NSCLC cells . Our data showed that the radiation of 2 Gy, which had no significant effect on cell proliferation , can significantly inhibit the wound healing of A549 (Fig. a) and H460 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Till date, several researches have demonstrated that miR-451a could inhibit the proliferation and differentiation of benign and malignant tumour cell and also affect the chemosensitivity of the tumour cells. Moreover, miR-451a in extracellular vesicles has been reported to influence the functions of immune cells, such as macrophages and dendritic cells [28,[33][34][35][36]. Hence, in the present study the predominantly enriched miR-451a in exosomes may be speculated to act as an important mediator in TRIM.…”
Section: Discussionmentioning
confidence: 49%
“…Several studies have reported the cancer suppressor activity of miR‐451a in other cancer types . miR‐451a was reported to inhibit aggressiveness features of lung squamous cell cancer by targeting KIF2A .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported the cancer suppressor activity of miR-451a in other cancer types. [21][22][23] miR-451a was reported to inhibit aggressiveness features of lung squamous cell cancer by targeting KIF2A. 24 In colorectal cancer, miR-451a was reported to inhibit proliferation and increase apoptosis by targeting BAP31.…”
Section: Discussionmentioning
confidence: 99%